Bacteriological and Mycological Assessments of Second-Hand Wears Procured From Girei And Jimeta Markets, Adamawa State, Nigeria - Halima Isa; Halima Isa; Nafisat Kachalla Adamu; Mohammed Bashir; Adamu Aliyu Usman; Simon Anthony; Blessing Wayeh (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt